1954
DOI: 10.1021/ja01639a076
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Cycloheptatriene

Abstract: Methods presently available1 for the preparation of cycloheptatriene (I) involve ring expansion of a six-carbon cycle as the key reaction step. We wish to report a novel and convenient synthesis of I which involves opening of the cyclobutane ring in a derivative of bicyclo [3.2.0jheptane. Reduction of the readily prepared (from cyclopentadiene and ketene)2 bicyclo [3.2.0]hept-2-ene-6-one with lithium aluminum hydride afforded (95%) bicyclo [3.2.0]hept-2-ene-6-ol (II), b.p. 96-98°( 38 mm.), k26d 1.4987 (Caled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1954
1954
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The rearrangement of these protonated bi-I cyclic ketones would most reasonably involve cyclopropylcarbinyl and allylcarbinyl intermediates, there being ample precedent for this in the products that have resulted from the io~~ization of related bicyclic systems in nucleophilic media (3,14). As is shown for 3H there are two ways in which the rearrangement of this cation could proceed that differ in the cyclobutane bond invol-ved.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The rearrangement of these protonated bi-I cyclic ketones would most reasonably involve cyclopropylcarbinyl and allylcarbinyl intermediates, there being ample precedent for this in the products that have resulted from the io~~ization of related bicyclic systems in nucleophilic media (3,14). As is shown for 3H there are two ways in which the rearrangement of this cation could proceed that differ in the cyclobutane bond invol-ved.…”
Section: Discussionmentioning
confidence: 97%
“…In practice only 4H was found as a product and no cation such as 13 could be detected. The auestion of which of the cvclobutane bonds will be involved in this type of rearrangement has been considered extensively in the solvolysis of related bicyclic systems (3,14) and it has been shown that the stereochemistry of the leaving group plays a major role in deternlining which bond is broken. However, with these long lived hydroxy cations such considerations have little meaning and additional factors nli~st be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Caled, for Ci8H20O: C, 81.2; H, 10.5. Found : C, 80.9; H, 10.7. 1,2,2a,7a-Tetrahydro-2,2-dimethyl-7H-cy clobut [a] inden-1 -one (13).-Under a nitrogen atmosphere, 70.0 g. (1.0 mole) of dimethylketene was added with stirring to a solution of 116.0 g.…”
Section: C4h9 23a 23bmentioning
confidence: 99%
“…h i b i t e d .hydro-2,2-dimethyl-7H-cyclobut[a]inden-l-one(13) in 12% yield. 1,3-Cyclooctadiene and butylethylketene Co + produce a 15% yield of a 1,2…”
mentioning
confidence: 99%
“…The infrared spectra of the two compounds, taken in the solid state, showed only minor differences in the fingerprint (800-1300 cm.-1) region which may be ascribed to the different crystal forms existing in the solid phase in the racemic and the optically active forms. 13 When the natural alkenylglycerol was converted into its liquid diacetate, both the n.m.r. and the infrared spectra of this and of the synthetic m-diacetate Vile were completely identical.…”
mentioning
confidence: 99%